2022
DOI: 10.3138/jmvfh-2021-0072a
|View full text |Cite
|
Sign up to set email alerts
|

How effectively does CBT-I address the traumatic and functional causes of insomnia and sleep disturbance in Veterans?

Abstract: LAY SUMMARY Cognitive-behavioural therapy for insomnia (CBT-I) continues to be recommended as the first-line treatment for an increasing number of Veterans seeking help for insomnia. Unfortunately, these recommendations are made on the basis of evidence from the general public, who do not experience the same predisposing, activating, and maintaining causes of insomnia as Veterans. This review considers whether CBT-I really addresses the causes of insomnia among Veterans, which can be labelled as functional (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Accordingly, this study evaluated outcomes for CBT‐I + IRT compared to CBT‐I alone for ex‐serving Australian Defence Force (ADF) personnel, in the context of PTSD and OSA risk. It was predicted that CBT‐I + IRT would lead to greater reductions in sleep disturbances than CBT‐I alone, as CBT‐I alone may not be able to address the functional and traumatic maintaining causes of insomnia in veteran populations (Rigley et al, 2022). This study used an IRT protocol with minimal exposure to nightmare content (Krakow & Zadra, 2006), in line with some uncontrolled studies that have reported improved outcomes for veterans (Nappi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, this study evaluated outcomes for CBT‐I + IRT compared to CBT‐I alone for ex‐serving Australian Defence Force (ADF) personnel, in the context of PTSD and OSA risk. It was predicted that CBT‐I + IRT would lead to greater reductions in sleep disturbances than CBT‐I alone, as CBT‐I alone may not be able to address the functional and traumatic maintaining causes of insomnia in veteran populations (Rigley et al, 2022). This study used an IRT protocol with minimal exposure to nightmare content (Krakow & Zadra, 2006), in line with some uncontrolled studies that have reported improved outcomes for veterans (Nappi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Different IRT protocols have been evaluated and they vary in their level of exposure to nightmare content, which may impact treatment tolerability for posttraumatic sleep disturbances (Harb et al, 2013). Additionally, a recent review argued that CBT-I may not be able to address the maintaining causes of sleep disturbances in veterans, including traumatic factors (e.g., hypervigilance and nightmares; Rigley et al, 2022).…”
mentioning
confidence: 99%